Exploring the Effects of the COVID-19 Pandemic on International Students and Universities in Canada - Firang, David; Mensah, Joseph (Journal of International Students, 2021)
International students in Canada make enormous contribution to the Canadian economy. As domestic students’ enrolment has declined, international students’ admissions have compensated for economic losses that Canadian universities incur from the decline of domestic students’ enrolment. The COVID-19 pandemic is impacting international students’ admissions to Canadian universities. Drawing on various secondary data sources, this article argues that international students in Canada are vulnerable due to their temporary immigration status. They are excluded from most governments’ relief programs aimed at supporting Canadians during this pandemic. Most international students experience psychological and financial difficulties amid the pandemic. The situation is triggering a further decline in international students’ admission, creating economic implications for Canadian universities. By exploring the challenges facing international students and the strategies required to strengthen international students’ resilience and universities’ capacities, the paper contributes to our understanding of the plights of international students and educational institutions amid the COVID-19 pandemic.